Determinants of the Incident of Pneumonia in Toddlers in Bengkulu City in 2020 - Wati, Nopia; Oktarianita, Oktarianita; Ramon, Agus; Husin, Hasan; J, Harsismanto (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The number of pneumonia cases in toddlers in Bengkulu City in 2018 reached 3,411. In 2017 there were 3,437 cases. In 2016 there were 31 people. The increase in pneumonia cases will affect the health status of infants and children in the future. This study aims to analyze the determinants of the incidence of pneumonia in children under five in Bengkulu City. The research method was cross-sectional, located in 4 health centers (Sukamerindu, Betungan, Telaga Dewa, and Kuala Lemembu). The sample in this study was 90 people. Data collection using a questionnaire. Data analysis by univariate and bivariate. Results, There is a relationship between immunization status (P-Value 0.000), exclusive breastfeeding (P-Value 0.004), history of ARI (P-Value 0.000), and residential density (p-value 0.004) with the incidence of pneumonia in children under five in Bengkulu City. The study concluded the significant relation between immunization status, exclusive breastfeeding, history of ARI, and residential density with the incidence of pneumonia in children under five in Bengkulu City. The most influential variable was exclusive breastfeeding.